Determination of radical scavenging activity and Vitamin A, C and E in organically grown Red Pitaya (Hylocereus sp.) - Rohin, Mohd Adzim Khalili; Ali, Abd Manaf; Abd. Hadi, Norhayati; -, Asmah (2010)
This study was conducted to determine radical scavenging activity and vitamin antioxidant composition in red pitaya from organic plantation. For antioxidant vitamins analysis, a reverse-phase high performance liquid chromatography was used and radical scavenging activity of methanolic and water extract were determined using 1,1-diphenyl-2-pircrylhydrazyl assay. Results for radical scavenging activity, red pitaya methanolic extract achieved the highest percentage 70.13% compared with water extract (47.13%). Antioxidant vitamins composition in red pitaya showed that the concentration of vitamin A is 120.13 ± 0.69 μg/100 g freeze-dried sample, vitamin C is 540.27 ± 0.59 μg/100 g fresh samples and vitamin E is 105.67 ± 0.56 μg/100 g freeze-dried samples. This shows that red pitaya may become an alternative and potential source of natural antioxidant.